The Addition of Cermai Fruit Strait (Phyllanthus Acidus) on THe Sensory Quality Of Gummy Candy - Julia Nooradilah; Mariani Mariani; I Gusti Ayu Ngurah Singamurni (Universitas Tanjungpura, 2023)
This study aims to determine the sensory quality of gummy candy by adding 20%, 40%, and 60% cermai or malay gooseberry juice. This research began in January 2022 at the Processing Laboratory of the Universitas Negeri Jakarta of Jakarta Culinary Art Education Study Program. This research used the experimental method. The sample in this study was gummy candy with 20%, 40%, and 60% cermai juice. Data collection in this study used a hedonic quality test, where 45 moderately trained panelists assessed all aspects of the sensory quality of cermai juice – gummy candy samples. Based on the results of statistical hypothesis testing, there was a significant effect on the aspects of cermai aroma, sweetness, cermai flavor, and sour taste, which was then continued with the Tukey test. The hedonic quality test and Tukey test showed that gummy candy with 60% cermai juice addition had the best sensory quality in gumminess, sweetness, cermai flavor, and cermai aroma.